Computational science and its applications – ICCSA 2017. 17th International Conference, Trieste, Italy, July 3-6, 2017, Proceedings /: 17th International Conference, Trieste, Italy, July 3-6, 2017, Proceedings. Part V : (2017) - Unknown
No abstract available